1995
DOI: 10.1021/es00006a029
|View full text |Cite
|
Sign up to set email alerts
|

Field Evaluation of in Situ Aerobic Cometabolism of Trichloroethylene and Three Dichloroethylene Isomers Using Phenol and Toluene as the Primary Substrates

Abstract: The Moffettfield site was used for further evaluation of in situ biotransformation of chlorinated aliphatic hydrocarbons with phenol and toluene as primary substrates. Within the 4 m test zone, representing a groundwater travel time of less than 2 days, removal efficiencies for 250 pg/L TCE and 125 pg/L ~is-1~2dichloroethylene were greaterthan 90%, and that of 125 pglL trans-l,2-dichloroethylene was -74%, when either 9 mg/L toluene or 12.5 mgIL phenol was used. Phenol and toluene were removed to below 1 p g l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
114
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(124 citation statements)
references
References 11 publications
6
114
1
3
Order By: Relevance
“…The results indicate that the toluene-utilizers stimulated would have the ability to cometabolize cis-DCE, however, TCE transformation was not clearly demonstrated. In previous field studies using toluene as a cometabolic substrate, cis-DCE was transformed more rapidly than TCE (Semprini et al 1994;Hopkins and McCarty, 1995). Results from the push-pull tests are consistent with these past well-to-well field tests.…”
Section: Transport Testsupporting
confidence: 77%
“…The results indicate that the toluene-utilizers stimulated would have the ability to cometabolize cis-DCE, however, TCE transformation was not clearly demonstrated. In previous field studies using toluene as a cometabolic substrate, cis-DCE was transformed more rapidly than TCE (Semprini et al 1994;Hopkins and McCarty, 1995). Results from the push-pull tests are consistent with these past well-to-well field tests.…”
Section: Transport Testsupporting
confidence: 77%
“…Previous reports suggested the use of glucose as co-substrate increased biodegradation rate (Swaminathan andSubrahmanyam 2002, Movahedin et al 2006). This process of co-metabolism is finding widespread applications in biodegradation management (Hopkins et al 1993, Hopkins andMcCarty 1995). Degradation of propiconazole by isolated tea rhizosphere microflora showed that these organisms adapted to this chemical because of repeated applications in field.…”
Section: Resultsmentioning
confidence: 99%
“…Field trials using these bacteria and/or the inducing substrates (e.g., phenol, toluene, and methane) for TCE bioremediation have also been reported previously (1-3, 12, 18, 19, 22, 27, 32, 35). However, since the enzymes involved in TCE transformation preferentially catalyze the genuine substrates (i.e., the inducers for TCE-degrading activity) rather than TCE, TCE is not always efficiently degraded in the presence of inducers such as phenol (7,14,21).…”
mentioning
confidence: 99%